2015
DOI: 10.3747/pdi.2013.00129
|View full text |Cite
|
Sign up to set email alerts
|

MgCaCO3 Versus CaCO3 in Peritoneal Dialysis Patients – a Cross-over Pilot Trial

Abstract: ORIGINAL ARTICLES♦ Background: Despite adverse effects such as constipation, vascular calcification, and hypercalcemia, calciumbased salts are relatively affordable and effective phosphate binders that remain in widespread use in the dialysis population. We conducted a pilot study examining whether the use of a combined magnesium/calcium-based binder was as effective as calcium carbonate at lowering serum phosphate levels in peritoneal dialysis (PD) patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…An asymptomatic, albeit significant, increase in serum magnesium occurred in the CaMg group as well. Another small clinical trial in peritoneal dialysis patients showed that CaMg was somewhat less effective than calcium carbonate in controlling serum phosphate, and, more importantly, that diarrhea appeared to be a more common dose-limiting adverse effect with CaMg 62 …”
Section: Dietary Phosphate Restrictionmentioning
confidence: 99%
“…An asymptomatic, albeit significant, increase in serum magnesium occurred in the CaMg group as well. Another small clinical trial in peritoneal dialysis patients showed that CaMg was somewhat less effective than calcium carbonate in controlling serum phosphate, and, more importantly, that diarrhea appeared to be a more common dose-limiting adverse effect with CaMg 62 …”
Section: Dietary Phosphate Restrictionmentioning
confidence: 99%
“…Of note, GI side effects were severe enough to limit effectiveness of MgCaCO 3 in only one study of 20 PD patients. Patients on MgCaCO 3 were only able to achieve 56% of the prescribed binder dose due to diarrhea as compared with 92% in the CaCO 3 group . Importantly, this was one of only two studies conducted in PD patients.…”
Section: Magnesium and Mineral Bone Disease In Dialysis Patientsmentioning
confidence: 90%
“…All other studies that used combination calcium‐magnesium binders have varied significantly with regard to calcium agent used (acetate vs carbonate), intervention allocation and comparator used (if any), outcomes studied (phosphate balance vs markers of systemic calcification), and reporting of side effects; all have generally included <50 patients . As a whole, these studies have demonstrated that phosphate binders consisting of calcium‐magnesium compounds were effective with respect to phosphate control, and that hypermagnesemia, if present, was generally mild and asymptomatic . Of note, GI side effects were severe enough to limit effectiveness of MgCaCO 3 in only one study of 20 PD patients.…”
Section: Magnesium and Mineral Bone Disease In Dialysis Patientsmentioning
confidence: 99%
“…Phosphate binders have proven effective in reducing serum phosphorus levels, but their use is often limited by adverse events (AEs) and/or heavy pill burden [ 9 ]. The reports that PD patients have poor control of serum phosphorus levels with existing phosphate binders [ 10 , 11 ] may indicate the involvement of subjective symptoms, such as abdominal fullness, diarrhea, and constipation. In fact, a study of Asian patients undergoing PD found that adherence to phosphate binder therapy was the only significant contributor to reduced serum phosphorus levels [ 12 ].…”
Section: Introductionmentioning
confidence: 99%